Enfants terribles. (Economist, 1999)
Focuses on the relationship between moral behavior and brain anatomy in light of the publication of a research paper in `Nature Neuroscience,' by Dr. Antonio Damasio and colleagues at the University of Iowa. Pre-frontal cortex injury and antisocial habits; Damasio's study of adults who suffered pre-frontal cortex injury as infants; Difference between infant and adult injury; Implications.